Cognitive Algorithms for Learning Foreign Languages: Psycholinguistics Approach - Koval, Natalia (Educational Challenges, 2021)
The relevance of the undertaken research consists in considering psycholinguistics an interdisciplinary field, which studies the interrelation between mind and language. It is important to perceive learning foreign language as an act of cognition, experience, and creativity in the psycholinguistic aspect of studying. Psycholinguistics concerns with the study of the cognitive process that supports the acquisition and use of language. The purpose of the paper is to reveal the importance of psycholinguistics approach and cognitive science for learning a foreign language in the context of psycholinguistic approach and cognitive methods for learning second language, based on achievements of the “Scientific School of A.V. Khutorsky”. Methodology is of an overview-analytical nature with an attempt to apply cognitive techniques to learning. Our observations on the psycholinguistic approach and the cognitive methods are based on the “Myth of Niels Bohr and the barometer question” by Alexander Calandra. Results. The analysis made it possible to determine how the logic of reflections has been explored from the lens of psycholinguistics and how the range of cognitive methods can be enlisted to learn a foreign language. It turns next to an overview of cognitive techniques used in psycholinguistics as applied to study. The verbal presentation of the idea is not only a form of compressed thought or interactive, creative cognition, but it also has a literary quality and makes use of a range of devices in a way. In the article, the solution formation reflects the features of transforming mental representations about the multidimensional space of life. Conclusions. According to the research, the paper concludes that cognitive methods are the ability to create judgments that are paradoxical in form and deep in content, perceived as deviating from the norm, and humor also presupposes the presence of the inverse ability to perceive such judgments in their entirety and depth and emotional brightness.